Meningkatkan kemampuan berhitung melalui metode jarimatika pada siswa kelas IV SDN 4 Telaga Jaya - Yesa Anggreni; Isnanto Isnanto; Andi Marshanawiah; Nur Sakinah Aries; Kudus Kudus (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
This study investigated whether the implementation of the Jarimatika method could improve multiplication skills among fourth-grade students at SDN 4 Talaga Jaya, Gorontalo Regency. The study aimed to enhance students’ multiplication abilities through the application of the Jarimatika method. A Classroom Action Research (CAR) design was employed, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 22 fourth-grade students. The research instruments included an achievement test to measure students’ multiplication skills and observation sheets to document teacher and student activities during the instructional process. Data were analyzed using descriptive quantitative analysis to calculate the percentage of students achieving the minimum mastery criterion (80%) and qualitative analysis to interpret observational data supporting the implementation process. The findings indicated a significant improvement in students’ multiplication skills. In Cycle I, 13 out of 22 students (59%) achieved mastery. After instructional refinement in Cycle II, the number increased to 19 students (86%), exceeding the predetermined mastery criterion. These results demonstrate that the Jarimatika method was effective in improving students’ multiplication skills. Practically, this study provides an alternative instructional strategy that is concrete, simple, and applicable for elementary school teachers to strengthen students’ understanding of multiplication concepts. Furthermore, the findings contribute to the existing body of knowledge on innovative mathematics instruction at the primary education level.